Financial Services Risk Management in The Context of a Pandemic - Feng Yongqiang; Denis Paleev (Communications of International Proceedings, 2021)
The article examines the impact of the COVID-19 pandemic on the financial stability of most enterprises. External and internal factors of financial risk of enterprises are studied. The key tasks of enterprise risk management and optimal directions in financial risk management in the context of a pandemic are described. The methods of optimizing the capital structure depending on the effectiveness of achieving the set goals according to the criteria are considered: maximizing the level of forecasting financial profitability; minimizing the cost of capital and the level of financial risks. The description of financial leverage is given.
Keywords: Risk Management; Pademia; Financial Risk; Financial Profitability.